2010
DOI: 10.1007/s10803-010-0951-9
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning in Children with Asperger Syndrome, ADHD-Combined Type, ADHD-Predominately Inattentive Type, and Controls

Abstract: The purpose of the study was to evaluate neuropsychological and behavioral rating measures of executive functions (EF) in children with two subtypes of ADHD, Asperger syndrome (AS), and controls. Relative to the control group, the clinical groups experienced more difficulty in EF. The AS group showed the most difficulty in emotional control, behavioral regulation, fluid reasoning, and planning compared to the ADHD groups. Number of symptoms of ADHD or AS was found to be significantly related to ratings of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 60 publications
5
92
0
4
Order By: Relevance
“…Continued difficulties as the child develops are observed in reduced number of social initiations and reciprocity in conversation and sustained conversation skills, compared to typically developing school aged children [5,6]. Finally, several studies have demonstrated reduced ability in individuals with ASD to recognize and correctly interpret emotional states from facial affect [7], vocal affect, [8], and video vignettes of interactions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Continued difficulties as the child develops are observed in reduced number of social initiations and reciprocity in conversation and sustained conversation skills, compared to typically developing school aged children [5,6]. Finally, several studies have demonstrated reduced ability in individuals with ASD to recognize and correctly interpret emotional states from facial affect [7], vocal affect, [8], and video vignettes of interactions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Executive dysfunction, especially in planning and abstract problem solving is also common in individuals with Asperger's syndrome (Hill and Bird 2006;Semrud-Clikeman et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the severity of ASD symptom does not necessarily correlate with subjective psychological stress or risk of psychiatric comorbidity since individuals with mild or atypical autistic traits may have been covertly suffering from mental health problems associated with interpersonal friction or maladaptation to society. Even if an adult patient does not have a medical history with an ASD diagnosis in childhood, repetitive discouraging experiences emotional dysregulation [108,109], executive dysfunction [51,110], and deficits in cognition of facial emotion [111], whereas BPD also comprises emotional dysregulation, executive dysfunction (i.e., impairments in attention, flexibility, learning, and planning), and deficits in cognition of facial emotion [112][113]. Additionally, another study showed that patients with ASD and patients with personality disorders (almost all subjects were patients with cluster B or cluster C personality disorder) did not differ in their ability to read and regulate emotions [114].…”
Section: Asd and Personality Disordersmentioning
confidence: 99%
“…Although deficits in executive functioning are not a specific feature of ASD individuals, they have more problems associated with executive dysfunction than healthy controls [108,129,130]. Furthermore, problems of executive dysfunction are not necessarily related to the severity of ASD symptoms [131][132][133].…”
Section: Difficulty In Diagnosing Mild Type Of Asdmentioning
confidence: 99%